Core–shell nanoparticles by silica coating of metal oxides in a dual-stage hydrothermal flow reactor. Issue 16 (2nd February 2016) - Hellstern, H. L.; Mamakhel, A.; Bremholm, M.; Iversen, B. B.
Abstract : A green, fast, high-throughput, continuous-flow hydrothermal synthesis method is explored for preparation of silica coated nanoparticles with narrow size distribution. Abstract : γ-Fe2 O3 @SiO2, TiO2 @SiO2, and α-Fe2 O3 @SiO2 core–shell nanoparticles were synthesized by a surfactant-free hydrothermal method in a continuous flow dual-stage reactor. Uniform silica shells of 2 nm thickness were obtained when grown on γ-Fe2 O3 and TiO2 nanoparticles while thicker and more irregular shells were deposited on α-Fe2 O3 due to low pH.